Misja dyplomatyczna Johna Jaya do Hiszpanii w latach 1779-1782. Oczekiwania i rozczarowania - Jakóbczyk-Adamczyk, Patrycja (Acta Universitatis Lodziensis. Folia Historica, 2001)
The article treats of the negotiations carried on by John Jay, the American Minister Plenipotentiary in Madrid, in 1780-1782. First of all the authoress analyses the Spanish attitude towards the question of the British colonies’ independence. The aim of J. Jay’s mission was to sign the Treaty of Alliance, Amity and Commerce. The instructions also obligated him to secure: 1) the right of free navigation on the Mississipi River, 2) the access to the Spanish ports below 31 of latitude and 3) the financial help. The negotiations with the Spanish Secretary of State, count of Floridablanca, was of no effect. Jay wasn’t admit as official representative of the American government. The instructions’ change in 1781 didn’t temper the Spanish attitude. Finally none of the aims was achieved. The United States obtained a little loan only. In the interests of the weak Spain was to keep balance, that is to weaken as much as possible the British power and to keep their colonies under the control of the metropolis at the same time. However the Spanish policy’s principle of festina lente missed an opportunity of advantageous settlement of two questions: the borders and the navigation on Mississipi. From 1783 they would be the dominant matters of argument between the neighbours.